2001
DOI: 10.1038/85507
|View full text |Cite
|
Sign up to set email alerts
|

Changing the dosing schedule minimizes the disruptive effects of interferon on clock function

Abstract: The effectiveness and toxicity of many drugs vary depending on the relationship between the dosing schedule and the 24-hour rhythms of biochemical, physiological and behavioral processes. In addition, several drugs can cause alterations to the 24-hour rhythms leading to illness and altered homeostatic regulation. However, the mechanisms of this drug-based disruption of circadian 'clock' genes remain unclear. Here, we show the disruptive effect of interferon-alpha on the rhythm of locomotor activity, body tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
127
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 36 publications
4
127
0
Order By: Relevance
“…The intensity of PCR product of the target gene was normalized to the intensity of ␤-actin. Reproducibility of the amplitude (ratio of peak to trough) and phase as determined by this method (19) suggested that the present experimental conditions were capable of detecting a circadian change of mPer1, mPer2, and mBmal1 gene expression in the mouse liver. SCN Lesion and Locomotor Activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of PCR product of the target gene was normalized to the intensity of ␤-actin. Reproducibility of the amplitude (ratio of peak to trough) and phase as determined by this method (19) suggested that the present experimental conditions were capable of detecting a circadian change of mPer1, mPer2, and mBmal1 gene expression in the mouse liver. SCN Lesion and Locomotor Activity.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA (100 ng) was reverse transcribed and amplified by using Superscript One-Step RT-PCR (Invitrogen) and GeneAmp PCR System 9700 (Applied Biosystems). We used primer pairs (4,19) that were designed on the basis of published data on mPer1, mPer2, mBmal1 (mouse brain and muscle ARNT-like 1 gene), and the ␤-actin gene in GenBank. PCR was executed under the following conditions: cDNA synthesis at 50°C for 30 min then 94°C for 2 min, PCR amplification for 28 cycles with denaturation at 94°C for 15 sec, annealing at 55°C for 30 sec, and extension at 68°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…In mammals, for example, several clock genes regulate circadian gene expression in central and peripheral clock tissues (3-9), as well as metabolites in the blood (10-15). Reflecting circadian regulation of such processes, the potency and toxicity of administered drugs depends on an individual's body time (BT) (16)(17)(18)(19)(20)(21)(22). Drug delivery according to body time improves the outcome of pharmacotherapy by maximizing potency and minimizing toxicity (23), and administrating drugs at an inappropriate body time can result in severe side effects (22).…”
mentioning
confidence: 99%
“…Reflecting circadian regulation of such processes, the potency and toxicity of administered drugs depends on an individual's body time (BT) (16)(17)(18)(19)(20)(21)(22). Drug delivery according to body time improves the outcome of pharmacotherapy by maximizing potency and minimizing toxicity (23), and administrating drugs at an inappropriate body time can result in severe side effects (22). For example, rhythm disturbances were induced by administration of IFN-α during the early active phase in mice, although unaffected during the early rest phase (22); and the time of administration of two anticancer drugs, adriamycin (6:00 AM) and cisplatin (6:00 PM), made a lower toxicity effect than its antiphasic administration (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation